Direct synthesis of 2-methylpyridines via I2-triggered [3 + 2 + 1] annulation of aryl methyl ketoxime acetates with triethylamine as the carbon source. Issue 13 (15th March 2018) - Gao, Qinghe; Yan, Huijuan; Wu, Manman; Sun, Jiajia; Yan, Xiqing; Wu, Anxin
Abstract : I2 -Triggered reductive generation of iminyl radicals for the synthesis of 2-methylpyridines by employing triethylamine as the carbon source. Abstract : A facile and efficient [3 + 2 + 1] annulation of aryl methyl ketoxime acetates and triethylamine for the synthesis of 2-methylpyridines was disclosed. This reaction demonstrated that I2 was effective in triggering N–O bond cleavage of oxime acetates generating imine radicals. It was noteworthy that this transformation employed triethylamine as the carbon source for the direct formation of pyridines and introduction of methyl groups.